2020
DOI: 10.1039/d0sm00207k
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of entrapped nanoparticles from thermoresponsive hydrogels with tunable network characteristics

Abstract: Thermoresponsive hydrogels have been studied intensively for creating smart drug carriers and controlled drug delivery. Understanding the drug release kinetics and corresponding transport mechanisms of nanoparticles (NPs) in a thermoresponsive hydrogel network is the key to the successful design of a smart drug delivery system. To investigate the anomalous NP diffusion in smart hydrogels with tunable network characteristics, we construct an energy-conserving dissipative particle dynamics model of rigid NPs ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…2 We note, however, that the two approaches predict qualitatively different behaviors for the relevant dynamical quantities, such as the NP diffusion coefficient as a function of C, see below for details. The importance of the confinement parameter for the description of the diffusion of NPs in polymer networks has also been confirmed in experiments 14,15,[52][53][54][55] and simulations. [42][43][44] However, even recent simulations 43,44 have not explored the strong confinement regime, C 3, due to the extremely slow dynamics that characterizes it and hence the dynamics of the NP in this range of parameters is at present not known.…”
Section: Introductionmentioning
confidence: 62%
“…2 We note, however, that the two approaches predict qualitatively different behaviors for the relevant dynamical quantities, such as the NP diffusion coefficient as a function of C, see below for details. The importance of the confinement parameter for the description of the diffusion of NPs in polymer networks has also been confirmed in experiments 14,15,[52][53][54][55] and simulations. [42][43][44] However, even recent simulations 43,44 have not explored the strong confinement regime, C 3, due to the extremely slow dynamics that characterizes it and hence the dynamics of the NP in this range of parameters is at present not known.…”
Section: Introductionmentioning
confidence: 62%
“…We point out interesting research directions that could involve the use of variableand distributed-order differential equations in the multi-scale modeling of materials. Recently, nano-scale simulation studies on trapping of nano-particles in hydrogel networks indicated a time-temperature dependency of the MSD in the evolution of anomalous diffusion regimes, where a subdiffusion regime has been found to be of transitional nature at intermediate time scales, with ballistic/normal diffusion dynamics for short/long time scales [236]. This motivates the study of variable-order models in time to compactly describe the macroscopic rheological evolution of such polymer networks.…”
Section: Future Directions In Modeling Anomalous Materialsmentioning
confidence: 99%
“…Two different mechanisms have been identified for the self-aggregation of temperature-responsive polymers during the coil-to-globule phase transition process, which is found to be dependent on the size of these polymer chains. Such a DPD model has been furthered applied to study the transport mechanisms of nanoparticles (NPs) in a thermoresponsive PNIPAM hydrogel network (Wang et al, 2020). By changing the simulation temperature across the LCTS of PNIPAM, the hydrogel network characteristics can be significantly altered, leading to the controlled release behaviors of entrapped NPs.…”
Section: Simulations Of Temperature-responsive Polymersmentioning
confidence: 99%